Month of birth of men with malignant germ cell tumours of the testis. Issue 3 (September 1986) - Bernstein, L; Chilvers, C; Murrells, T; Pike, M C
Abstract : A recent paper has suggested that there is a temporal cycle in birth rates of men with testis cancer with a peak in April/May. We have investigated the suggestion using data from the South Thames and Los Angeles cancer registries. There is some slight evidence of a peak in August, which is confined to teratomas. The effects demonstrated are, however, too small and inconsistent to provide any real clue to the aetiology of testis cancer.